2012
DOI: 10.1007/s00113-012-2157-4
|View full text |Cite
|
Sign up to set email alerts
|

Implantatentfernung nach Beckenringfraktur

Abstract: In some cases like external fixation, implant-associated infection, malpositioning, allergic implant reaction, critical soft tissue covering, palpable hardware and consolidated juvenile fractures implant removal is certainly indicated. In patients without symptoms and in patients with trauma-associated symptoms which are not definitely associated with the hardware, the removal should be only indicated after thorough consideration of the risks versus the benefits and additionally by taking the initial injury pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
1
10
0
1
Order By: Relevance
“…Complication rates and kinds (refractures, wound infections or nerve damages) differ with various implants and body sides. Furthermore documentation of the complications and study design are heterogeneous [ 7 , 9 12 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complication rates and kinds (refractures, wound infections or nerve damages) differ with various implants and body sides. Furthermore documentation of the complications and study design are heterogeneous [ 7 , 9 12 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence indicating that the postoperative complication rate depends on the specific localization of the implanted material. However, inter-individual differences are significant and published data still lacks consistency [ 7 – 12 ]. Therefore general recommendations cannot yet be established.…”
Section: Introductionmentioning
confidence: 99%
“…Das primäre Therapieziel instabiler Beckenfrakturen besteht daher in der raschen Stabilisierung des Beckens als lebensrettende Maßnahme zur Reduktion pelviner Blutungen. Die definitive Rekonstruktion erfolgt meist anschließend in der sekundären Operationsphase [7]. Bislang werden v. a. Untersuchungen geführt, die auf eine Verbesserung der Überlebenswahrscheinlichkeit in der Akutphase abzielen.…”
unclassified
“…In their case series on implant removal from the anterior and posterior pelvis, Stuby et al [15] observed procedure-related complications in 20%.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors see an indication for removal only in case of complications [9, 20], others recommend implant removal routinely [7, 21]. Only about a third of the symptomatic patients report sufficient relief of their complaints after the procedure [15]. In addition, many patients ask for removal without being symptomatic.…”
Section: Introductionmentioning
confidence: 99%